2008
DOI: 10.23818/limn.27.15
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of exotic fish species in the Guadiana river basin, with two new records

Abstract: Spatial distribution of exotic fish species in the Guadiana river basin, with two new recordsThis work updates the spatial distribution of the exotic fish species in the Guadiana river basin. To this effect, 241 river stretches and 37 reservoirs and lakes were sampled, corresponding to 261 UTM 10 × 10 Km squares. A total of 12 exotic species were found, including two new species that had not been previously cited in the area, the channel cat-fish (Ictalurus punctatus) and the roach (Rutilus rutilus). These two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Correspondingly, a recent study investigating global fish distributions revealed that the historical connection among river basins during Quaternary low sea‐level periods constitutes a good predictor explaining range sizes in freshwater fishes (Carvajal‐Quintero et al, 2019). Although its effect is not as remarkable as for primary native species, ‘basin ID’ was also the most important variable for several alien species such as Australoheros facetus , mostly present in the Guadiana basin (Hermoso et al, 2008); and Scardinius erythrophthalmus , whose distribution is mainly restricted to the basins of the Ebro and Eastern Pyrenees (Doadrio, 2001). By contrast, ‘basin ID’ was much less important for peripheral fish, as their geographical ranges are not necessarily restricted by the sea given their ability to migrate, or disperse through seawater (McDowall, 2010) and thereby enter and colonize other river catchments.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, a recent study investigating global fish distributions revealed that the historical connection among river basins during Quaternary low sea‐level periods constitutes a good predictor explaining range sizes in freshwater fishes (Carvajal‐Quintero et al, 2019). Although its effect is not as remarkable as for primary native species, ‘basin ID’ was also the most important variable for several alien species such as Australoheros facetus , mostly present in the Guadiana basin (Hermoso et al, 2008); and Scardinius erythrophthalmus , whose distribution is mainly restricted to the basins of the Ebro and Eastern Pyrenees (Doadrio, 2001). By contrast, ‘basin ID’ was much less important for peripheral fish, as their geographical ranges are not necessarily restricted by the sea given their ability to migrate, or disperse through seawater (McDowall, 2010) and thereby enter and colonize other river catchments.…”
Section: Discussionmentioning
confidence: 99%
“…The summation of all the metrics scores obtained guided to materializing the outcome as the final IBI score that later represented the biological integrity classes. The biotic integrity classes and their ranges based on IBI scores are: excellent (36)(37)(38)(39)(40), good (28)(29)(30)(31)(32)(33)(34), fair (20)(21)(22)(23)(24)(25)(26), poor (14)(15)(16)(17)(18) and very poor (8-13).…”
Section: Ecological Health Assessmentmentioning
confidence: 99%
“…The anthropogenic disturbances reportedly facilitate successful fish invasions in the disturbed ecosystems [56]. It appears that IAFS prefer the lentic habitats with hydrological disturbances such as dam construction [17,57] and weir impacts [21] for their rapid spread and concomitant establishment. The construction of the weir on streams and rivers regularly hinders the water currents, leading to unexpected micro-habitat structure changes [58].…”
Section: Water Chemistry and Physical Habitat Qualitymentioning
confidence: 99%
See 2 more Smart Citations